CONVENTIONAL RADIOGRAPHY ANALYSIS OF 70 CASES OF PROVED APPENDICULAR-SKELETAL-RELATED OSTEOSARCOMA IN RAMATHIBODI HOSPITAL - SIRIWONGPAIRAT, Pimjai; KITTIPERACHOL, Sarawoot; PEKANAN, Patchrin; POCHANUGOOL, aksana; JAOVISIDHA, Supaneewan; JATCHAVALA, Janjira (The ASEAN Journal of Radiology, 2023)
A retrospective analysis of conventional radiographic appearance of the appendicu- lar skeletal related osteosarcoma patients, who came for pre-operative chemoembolization was presented in 70 cases. The most common age range was 16-20 years old. Male to female ratio was 1.3 to 1. The presenting symptoms were pain and soft tissue mass. Central osteosarcoma occupied 90% of cases and the rest was its variant-telangiectatic type. Around knee involvement was the most common area. Long bones predominated with rare flat bones involvement. Every region of the bone may be involved, but 85% included metaphyseal region. There was no isolated epiphyseal involvement. Usually the radiographic pattern was mixed lytic and blastic and purely lytic lesion. There was no good correlation between the roentgen appearance and the histologic type. The osteoid matrix represented 74%, chondroid matrix 14% and unclassified 13%. 81% had associated mass, and more than half of them were larger than 5 cms. The sunburst or sunray, the Codman's triangle or combined pattern represented 66%, the rest was spiculated pattern and combined spiculated and Codman's triangle. The finding were not different from those reported by previous authors, except epiphyseal plates were involved mainly in young children whose growth plates were not closed.